SYSTEMATIC LITERATURE REVIEW: POTENSI MEDIA KOMIK DALAM MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SMP - Nabilah Aniqah Putri; Heni Pujiastuti; Ria Sudiana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research is motivated by the tendency of students to memorize procedures without understanding the essence of the material, as well as the low national basic mathematical competency based on the TIMSS report. The focus of this research problem is to map the potential for systematic use of comics media in boosting students' mathematical understanding abilities at the Junior High School (SMP) level. Using the Systematic Literature Review (SLR) method, a crucial step in the research was carried out by screening nationally accredited articles (SINTA 1–6) from the Ministry of Education and Culture database between 2021 and 2026. Based on strict inclusion criteria, 25 relevant articles were obtained, which were then analyzed using a thematic matrix approach. The research findings revealed that the integration of visual narratives in comics effectively transformed students' mathematics quality holistically through three main dimensions. In the basic cognitive cluster, comics were proven to significantly improve conceptual learning outcomes from the average pre-test to post-test scores evenly. In the advanced cognitive cluster, the combination of comics with PBL and STEM syntax successfully triggered the sharpness of critical thinking, creativity, and numeracy literacy. Affectively, the dominance of positive student responses exceeding 80 percent confirms that comics are able to reduce mathematical anxiety while simultaneously fostering enjoyable learning independence. ABSTRAK Penelitian ini dilatarbelakangi oleh kecenderungan siswa yang menghafal prosedur tanpa memahami esensi materi, serta rendahnya kompetensi dasar matematis nasional berdasarkan laporan TIMSS. Fokus masalah dalam riset ini adalah memetakan potensi penggunaan media komik secara sistematis dalam mendongkrak kemampuan pemahaman matematis siswa pada tingkat Sekolah Menengah Pertama (SMP). Melalui metode Systematic Literature Review (SLR), langkah penting penelitian dijalankan dengan menyaring artikel terakreditasi nasional (SINTA 1–6) dari basis data Kemendikbud dalam rentang waktu tahun 2021 hingga 2026. Berdasarkan kriteria inklusi yang ketat, diperoleh 25 artikel relevan yang kemudian dianalisis menggunakan pendekatan matriks tematik. Temuan riset mengungkapkan bahwa integrasi narasi visual dalam komik efektif mentransformasi kualitas matematika siswa secara holistik melalui tiga dimensi utama. Pada klaster kognitif dasar, komik terbukti signifikan meningkatkan hasil belajar konseptual dari rata-rata nilai prates menuju pascatest secara merata. Pada klaster kognitif tingkat lanjut, kombinasi komik dengan sintaks PBL dan STEM sukses memicu ketajaman berpikir kritis, kreatif, serta literasi numerasi. Secara afektif, dominasi respon positif siswa melampaui 80 persen mengonfirmasi bahwa komik mampu mereduksi kecemasan matematis (math anxiety) sekaligus menumbuhkan kemandirian belajar yang menyenangkan.